PENGARUH MODEL SIKLUS BELAJAR 5E TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V SDN GUGUS X KECAMATAN NARMADA TAHUN PELAJARAN 2018/2019 - Rahayu Yurni Ani; Ahmad Harjono; L. Hamdian Affandi (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2020)
This research is in the background behind the learning method used by the fifth grade teacher of SDN Cluster X in Narmada Subdistrict in the learning process which is still centered on the teacher as the informer. This type of research is an experimental study which aims to determine the effect of the 5E learning cycle model on the learning outcomes of science students of class V SDN Cluster X Narmada Subdistrict 2018/2019 academic year. This study uses an experimental quantitative method, a type of quasi experimental type of nonequivalent control group design. The population in this study were all fifth grade students of SDN Cluster X of Narmada Subdistrict, amounting to 137 students. The sampling technique used was purposive sampling technique with a sample of 48 students. Data collection techniques used in this study were tests and observations. Data analysis methods used t-test with prerequisite test, namely normality test and data homogeneity test. After analyzing the data obtained the results of tcount 3.596>2.020 ttable at the significance level of 5%, so, it can be concluded that there is an influence of the 5E learning cycle model on science learning outcomes of fifth grade students of SDN Cluster X Narmada Subdistrict 2018/2019 Academic Year. Based on t polled variance (tcount), the effect size of the 5E learning cycle model for the students' learning outcomes of science students of class V SDN Cluster X Narmada Subdistrict 2018/2019 academic year was 21.9%..